Neurogenesis of Professional Destructions of Personality - Virna, Jeanne Petrivna (Psychological Prospects Journal, 2012)
The article shows the theoretical analysis of professional destructions of personality concerns consideration of neurotic signs of strain through double professional ethical standards, professional and occupational burnout margins and professional addictions through workaholism, perfectionism and urgent professional relationship.